Influence of magnetic domain walls on all-optical magnetic toggle switching in a ferrimagnetic GdFe film - Hosseinifar, Rahil; Golias, Evangelos; Kumberg, Ivar; Guillet, Quentin; Frischmuth, Karl; Thakur, Sangeeta; Fix, Mario; Albrecht, Manfred; Kronast, Florian; Kuch, Wolfgang (Beilstein Journal of Nanotechnology, 2022)
We present a microscopic magnetic domain imaging study of single-shot all-optical magnetic toggle switching of a ferrimagnetic Gd26Fe74 film with out-of-plane easy axis of magnetization by X-ray magnetic circular dichroism photoelectron emission microscopy. Individual linearly polarized laser pulses of 800 nm wavelength and 100 fs duration above a certain threshold fluence reverse the sample magnetization, independent of the magnetization direction, the so-called toggle switching. Local deviations from this deterministic behavior close to magnetic domain walls are studied in detail. Reasons for nondeterministic toggle switching are related to extrinsic effects, caused by pulse-to-pulse variations of the exciting laser system, and to intrinsic effects related to the magnetic domain structure of the sample. The latter are, on the one hand, caused by magnetic domain wall elasticity, which leads to a reduction of the domain-wall length at features with sharp tips. These features appear after the optical switching at positions where the line of constant threshold fluence in the Gaussian footprint of the laser pulse comes close to an already existing domain wall. On the other hand, we identify the presence of laser-induced domain-wall motion in the toggle-switching event as a further cause for local deviations from purely deterministic toggle switching.
Keywords: all-optical magnetic switching; GdFe; laser-induced domain-wall motion; magnetic domain imaging; photoemission electron microscopy